APLIKASI STRATEGIS ANALISA SWOT (KOMBINASI ANTARA TEORI DAN KONDISI LAPANGAN) - Sahat M.P. Tanjung (Sekolah Tinggi Ilmu Ekonimi IPWI Jakarta, 2017)
In all of applications of various kinds of tools at management field there are many variances have been found out.There is a tendency among people to leave many tools that have been known and used in the past by the upcoming new ones found later on in the progress. One of them is the so called SWOT Analysis.But this analysis that practically have been widely deemed as old fashioned actually have been used very successfully until today. At the 80 decades this analysis have shown that it had helped such a big and worlwidely company named Apple Computer Company saved from its fall by the reemergence of IBM who survived to produce also the personal computers.The SWOT Analysis is a very practical tool. It does not need a special or sophisticated equipment. It also does not require any special trained personnel to work with and it is very easily understood by everyone.This combined comparison between the theory and the strategic applications of SWOT Analysis is written by explorative method, confirming the great necessity still needed up to now about the daily usage.The analysis comprises the big two types named the Traditional one and the Matrix type. Any of the usage is depended on the dominant element of the SWOT appeared in practices.Keywords:Â Strategic Management, SWOT, Strategic Applications, Traditional type analy- sis, Matrix type analysis.